The Effect of Rambutan’s Leaf Extract Inhibitor on Corrosion Rate on Cast Iron Block Car Sedan Nissan in HCl Solution 1% - Ismet Eka Putra; Pren Tanjung (Jurnal Teknik Mesin, 2020)
Corrosion in cast iron can be overcome by rambutan counter measures (Nepheliumlappaceum.L). The object of the study which is placed in 1% HCl solution each of 3 specimens in 1 vessel. 12 specimens in 4 vessels. In this study, soaking iron cast iron car block Sedan Nissan without inhibitor and the variation of inhibitor 5%, 10%, and 15% with immersion time 5, 10, and 15 days. The solution is coincides with 0.095 m3/hr of passage in a vessel with a volume of 1% 900 ml of HCl. The highest corrosion rate in cast iron soaked in 1% HCl without using rambutan leaf extract and immersion time of 15 days is 0,075054 mpy. The lowest corrosion rate in cast iron soaked in 1% HCl solution using 15% rambutan leaf extract and a 15 day immersion time of 0,025863 mpy.